2010
DOI: 10.1364/ao.49.006236
|View full text |Cite
|
Sign up to set email alerts
|

High-power widely tunable thulium fiber lasers

Abstract: Applications requiring long-range atmospheric propagation are driving the development of high-power thulium fiber lasers. We report on the performance of two different laser configurations for high-power tunable thulium fiber lasers: one is a single oscillator utilizing a volume Bragg grating for wavelength stabilization; the other is a master oscillator power amplifier system with the oscillator stabilized and made tunable by a diffraction grating. Each configuration provides >150 W of average power, >50% slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…In addition, tunability of basic TDF lasers in the 2.0 mm wavelength region has already been widely demonstrated by using volume Bragg gratings (VBGs) [29][30][31], and also by the use of diffraction gratings [18,32]. However, these methods are quite complex due to the use of bulky optic components in the laser cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tunability of basic TDF lasers in the 2.0 mm wavelength region has already been widely demonstrated by using volume Bragg gratings (VBGs) [29][30][31], and also by the use of diffraction gratings [18,32]. However, these methods are quite complex due to the use of bulky optic components in the laser cavity.…”
Section: Introductionmentioning
confidence: 99%
“…The suspended core structure is a feasible way to realize wide band ZDW shift [2]. Recently, thulium-doped fiber lasers (TDFLs) provide highquality lasing from 1.8 to 2.1 μm with high average power and high slope efficiency [3], which becomes a promising choice to serve as the pump of a chalcogenide FOPO. In this paper, we proposed a MIR FOPO using a three-hole As2S5 suspended-core fiber (SCF) with a core diameter of 2.6 μm as the gain medium.…”
Section: Introductionmentioning
confidence: 99%
“…McComb et al reported the performance of a laser configuration for high power tunable TDFL. The fiber laser was based on a master oscillator power amplifier system with the oscillator stabilized and tuned by a diffraction grating [5]. Li et al achieved a direct diode-pumped all-fiber tunable laser source at 2-μm band with a tuning range of more than 250 nm [6].…”
Section: Introductionmentioning
confidence: 99%